Application of Open and Distance Learning in Positioning Nigerian Educational System for Sustainable National Development - Aliede, Jonathan E. (West African Journal of Open and Flexible Learning, 2018)
Globally, universities are seen as centres for evolving ideas, mechanisms and strategies for positioning nations on the part of enduring development. Indeed, they are the pivot for implementing Sustainable Development (SD). The concept of sustainable development which is the hallmark of the United Nations’ Millennium Development Goals (MDGs) has as part of its main objectives the eradication of extreme poverty; achievement of universal primary education and promotion of gender equality and women empowerment, ends that cannot be attained without effective and functional tertiary educational system. Yet, the conventional system seems to be incapable of contributing to its attainment; hence an alternative mode is required. Open and Distance Learning mode of education seems to be the answer. This study, therefore, while focusing on the National Open University of Nigeria (NOUN) used qualitative and contextual methods to examine how the institution’s ODL system of education is aiding Nigeria’s achievement of sustainability. Its findings included that the ODL mode has a lot of potentials and inbuilt devices favourable to aiding NOUN in putting Nigeria on the part of sustainable development, though the system faces some challenges. It, therefore, recommended adequate funding and staffing; provision of infrastructure and further expansion of the mode of education in order to assist NOUN pursue the objective. Résumé : À l'échelle mondiale, les universités sont considérées comme des centres d'évolution des idées, des mécanismes et des stratégies pour positionner les nations sur la ligne du développement durable. En effet, elles sont le pivot de la mise en œuvre du développement durable (DD). Le concept de développement durable, qui est la marque des Objectifs du Millénaire pour le développement (OMD) des Nations Unies, a pour objectif principal d'éradiquer l'extrême pauvreté ; l'éducation primaire universelle et la promotion de l'égalité des sexes et de l'autonomisation des femmes, des objectifs qui ne peuvent être atteintes sans un système d'enseignement supérieur efficace et fonctionnel. Pourtant, le système conventionnel semble incapable de contribuer à sa réalisation ; par conséquent, un mode alternatif est nécessaire. Le mode de formation ouverte à distance semble être la réponse. Cette étude, par conséquent, tout en se concentrant sur l'Université nationale ouverte du Nigeria (NOUN) a utilisé des méthodes qualitatives et contextuelles pour examiner comment le système d'éducation de l'ODL de l'institution contribue à la réalisation de la durabilité au Nigéria. Il a été conclu que le mode ODL a beaucoup de potentiels et de dispositifs intégrés favorables à aider NOUN à mettre le Nigeria sur la ligne du développement durable, bien que le système soit confronté à certains défis. L’étude recommande un financement et une dotation adéquats ; l'infrastructure et l'expansion du mode d'éducation afin d'aider NOUN à poursuivre l'objectif.